2015
DOI: 10.1371/journal.pone.0122121
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and Porphyromonas gingivalis in Preclinical Stage of Arthritis Patients

Abstract: PurposeTo determine whether the presence of periodontitis (PD) and Porphyromonas gingivalis (Pg) in the subgingival biofilm associates with the development of rheumatoid arthritis (RA) in treatment naïve preclinical stage of arthritis patients.MethodsWe conducted a prospective cohort study of 72 consecutive patients with arthralgia who had never been treated with any anti-rheumatic drugs or glucocorticoids. Periodontal status at baseline was assessed by dentists. PD was defined stringently by the maximal probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 37 publications
(56 reference statements)
4
38
0
7
Order By: Relevance
“…Microbiologic aspects are increasingly discussed in the literature as a potential connecting factor between periodontitis and RA. In this context, high prevalence of typical periodontopathogens could be shown; 18 however, differences in composition of subgingival biofilm were only partially detected in comparing RA and HC groups 21 , 34 . The current study found higher concentrations and prevalence rates of F. nucleatum and P. micra in patients with RA as well as positive findings of T. denticola in multivariate analysis within the RA group.…”
Section: Discussionmentioning
confidence: 38%
“…Microbiologic aspects are increasingly discussed in the literature as a potential connecting factor between periodontitis and RA. In this context, high prevalence of typical periodontopathogens could be shown; 18 however, differences in composition of subgingival biofilm were only partially detected in comparing RA and HC groups 21 , 34 . The current study found higher concentrations and prevalence rates of F. nucleatum and P. micra in patients with RA as well as positive findings of T. denticola in multivariate analysis within the RA group.…”
Section: Discussionmentioning
confidence: 38%
“…More advanced forms of periodontitis were found in patients with early RA compared with controls [2]. A recent Japanese study showed that periodontitis in treatment-naïve arthralgia patients was significantly associated with arthritis activity and the later need for methotrexate treatment upon diagnosis of RA [4]. RA has also been associated with tooth loss and periodontitis [3], and oral health-related quality of life is reported to be poor in patients with RA [5].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Japanese study showed that periodontitis in treatment-naïve arthralgia patients was significantly associated with arthritis activity and the later need for methotrexate treatment upon diagnosis of RA [4]. Oral health-related quality of life is reportedly poor in patients with RA [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tyrimai parodė, kad lėtinis PD yra susijęs su didesniu RA aktyvumu ir greičiau besivystančiais bei labiau išreikštais radiologiniais sąnarių pažeidimo požymiais [49,52].…”
Section: P Gingivalis Ir Raunclassified